ИСПОЛЬЗОВАНИЕ ЭКОНОМИЧЕСКИХ МОДЕЛЕЙ В УЧЕБНОМ ПРОЦЕССЕ. (Journal of Economic Research & Business Administration, 2016)
The article examines possibilities of using well-known economic models and indexes for improving educational process at KazNU named after al-Farabi.